Immigration, language education, & trauma: exploring the intersectionality of gay Dominican immigrant experiences - González, Jordan (Frontiers in Sociology, 2025)
This article explores the intersectionality of immigration, language education, and trauma among gay Dominican immigrant men living in New York City. Utilizing a qualitative case study approach, the research examines the lived experiences of four individuals, highlighting the compounded adversities they face due to their intersecting identities as LGBTQ+, men of color, and immigrants. The case studies reveal significant trauma and mental health struggles stemming from pre-migration violence, in-transit dangers, and post-migration discrimination. Additionally, the study addresses the critical role of language proficiency in their integration and the importance of tailored support systems, including community networks and legal protections. The findings underscore the severe impact of discrimination based on sexual orientation, race, and immigration status on the mental health and social integration of gay Dominican immigrant men. Despite these challenges, the participants demonstrate remarkable resilience and hope for the future, striving for better employment opportunities, educational advancement, and community belonging. This article provides insights into the specific needs of LGBTQ+ immigrants and offers recommendations for improving support systems, policies, and educational practices to better serve this vulnerable population.